Influence of the Sawing Method on Yield of Beech Logs with Red Heartwood - Ranko Popadić (University of Zagreb, Faculty of Forestry and Wood Technology, 2014)
The paper presents the research of differences in quantitative and value yields, and structure of sawn timber and residues, whose appearance is caused by different methods of sawing beech logs with red heartwood. In order to achieve the goal, 45 logs were divided into three even groups and sawn into commercial timber using three methods: round, cant and live sawing. Similar quantitative yields were found for round sawing and cant sawing (60.63 % and 60.52 %, respectively), while a lower result of 56.79 % was observed for live sawing. Less timber (edged and red heartwood boards) and smaller products were found in live sawing than in other two methods, meaning that live sawing resulted in a lower value yield.